Incidence of deep venous thrombosis in COVID-19 hospitalized patients during the first peak of the Italian outbreak. (June 2021) - Baccellieri, Domenico; Bertoglio, Luca; Apruzzi, Luca; Ardita, Vincenzo; D'Angelo, Armando; Bossi, Matteo; Rinaldi, Enrico; Bilman, Victor; Calvisi, Stefania; Castagna, Antonella; Galli, Laura; Landoni, Giovanni; et al.
Objectives: A high rate of thrombotic events has been reported in COVID-19 population. The study aims to assess the incidence of deep vein thrombosis (DVT) in COVID-19 patients admitted to a single tertiary hospital. Methods: From April 2nd to April 18th, 2020, hospitalized patients with SARS-CoV-2 infection were screened by lower limb duplex ultrasound (DUS). Patients were on (low molecular weight heparin) LMWH prophylaxis in medical wards, and on therapeutic anticoagulation in intensive care unit (ICU). DVT risk factors, reported by the Padua prediction score and blood tests, were retrieved from institutional electronic charts. The study primary endpoint was the incidence of DVT in the in-hospital COVID-19 population and its association with clinical and laboratory risk factors. The secondary endpoint was the association of DVT with mortality. Results: Two hundred patients (median age 62 years, 72% male, 40 in ICU) received DUS screening. DVT was observed in 29 patients (14.5%), with proximal extension in 16 patients, and in association with symptoms in four patients. The DVT rate was similar in ICU (12.5%) and non-ICU patients (15%). Eighty-seven patients underwent a computed tomography angiography (CTA) that showed pulmonary embolism in 35 patients (40.2%) not associated with DVT in 25/35 cases (71.4%). DVT in the ten patients with pulmonary embolism were symptomatic in four and with a proximal localization in eight cases. A D-dimer level ≥5 mg/l at admission was predictive of DVT (OR 1.02; IC95% 1.03-1.16; p  = .003). At the multivariate analysis in-hospital mortality was predicted by age (OR 1.06; 95% CI 0.02-1.15; p  = .004) and by being an ICU patient (OR 1.23; 95% CI 0.30-2.25; p  = .01). Conclusions: Despite LMWH prophylaxis or full anticoagulant therapy, the incidence of DVT, mainly asymptomatic, in hospitalized COVID-19 patients was 14.5%. Further research should focus on the appropriate antithrombotic therapy for COVID-19 patients.